ANALISIS HUKUM TERHADAP PROSEDUR DAN JANGKA WAKTU PENANGANAN PERKARA ATAS LAPORAN POLISI NOMOR STTLP/2298/K/X/2018/SPKT POLRESTA MEDAN BERDASARKAN PERATURAN KAPOLRI NO. 12 TAHUN 2009 - MASLON HUTABALIAN (Universitas Quality, 2021)
The Indonesian National Police Institution is a State institution established based on LawNumber 2 of 2002 which functions as one of the functions of the state government in thefield of maintaining security and public order, law enforcement,protection, shelter, andservice to the community, as stated in Article 2 Law no. 2 of2002. This means thatthe police are fully responsible for providing security and order guarantees to allmembers of the community. In its development and practice, in general, this function hasnot been felt by all people, especially justice seekers who experience legal problems,either directly or indirectly, so that satisfaction with the police services cannot becategorized as adequate.Although in terms of implementation and implementation in thefield, it has been regulated in such a way as the basis or what is called StandardOperating Procedure (SOP) in this case, one of which is related to the Regulation of theNational Police Chief No. 12 of 2009 concerning the supervision and control of thehandling of criminal cases within the Indonesian National Police. This study aims todetermine how the procedure in handling a police report at the investigation level is andhow long the period of time in handling a police report is. This study will explore andlegally analyze the duration of handling a police report associated with the reportNumber STTLP/ 2298/ K/ X/2018/ SPKT Medan Polresta based on the National PoliceChief Regulation No. 12 of 2009 concerning the supervisionand control of the handling ofcriminal cases within the police.This study uses normative and empirical researchmethods consisting of research on legal observations and research on legal effectiveness.This study uses an interrelated concept, namely data collection through a qualitativeapproach and adapted to the applicable regulations. Then the data is selected bycollecting various information about the process of handling a case and the duration ofits handling at the investigation level. This research is expected to have a mandatoryoutput that is planned in the Justiqa Journal of Quality University